Palaeocurrents and provenance of the Mae Rim Formation, Northern Thailand: Implications for tectonic evolution of the Chiang Mai basin - Brady P. Rhodes (2018)
The Chiang Mai basin is the largest of a zone of rift basins that define the Northern Thailand Basin and Range Province. This province lies within the Shan Thai block of NW Indochina that extruded out of the India-Asia collision. The Mae Rim Formation crops out along the western side of the Chiang Mai basin. Detachment faults border the Mae Rim Formation on the west and north and juxtapose it against the high-grade Western Ranges metamorphic complex and its low-grade cover of Palaeozoic Shan-Thai rocks. Understanding the age and tectonic relationships between rifting, detachment faulting, ductile shear, uplift and exhumation of the Western Ranges metamorphic complex is critical to understanding the underlying deformational mechanisms that accompanied Indochina's extrusion. To better understand the palaeogeography of the Chiang Mai basin and its relationship to the Western Ranges metamorphic complex, several partial sections were measured, and palaeocurrent and clast-composition data from the Mae Rim Formation were collected. Poorly organized, immature conglomerates of the Mae Rim Formation probably represent alternating debris flows, sheet-flood, and braided channel deposits. The Mae Rim Formation probably accumulated in range-front alluvial fans, and graded rapidly into lacustrine deposits within the buried central part of the Chiang Mai basin. Except for the youngest strata, where gneissic clasts predominate, virtually all clasts in the Mae Rim Formation came from the low-grade metasedimentary rocks that form the cover of the Western Ranges metamorphic complex. Imbricated clasts indicate eastward palaeocurrents away from the metamorphic complex. Most of the Mae Rim Formation accumulated during the uplift of the Western Ranges but before erosion had breached the detachment fault. These new data suggest a tectonic history for the Chiang Mai basin that involved distinct phases of extension from late Oligocene to Quaternary, with at least two intervening periods of basin inversion.